Decreased emotional creativity and its relationship with cognitive functions in Parkinson's disease: A preliminary study. Issue 6 (2nd November 2022) - Nikolai, Tomas; Sulc, Zdenek; Balcar, Karel; Kuška, Martin; Plzakova, Vladimira; Slavickova, Tereza; Trnka, Radek
Abstract: Patients with Parkinson's disease (PD) suffer from a wide range of non-motor symptoms, including cognitive deficits and impairment of emotional processing. The present study aimed to explore in PD patients compared to healthy adults the relationship between cognitive performance and emotional creativity (EC), defined as a set of cognitive abilities and personality traits related to originality and appropriateness of emotional experience. PD patients ( n  = 22) and healthy controls ( n  = 40) underwent a complex neuropsychological assessment and were administrated with the self-reported Emotional Creativity Inventory (ECI) questionnaire. To explore the relationship between cognitive tests and the ECI, a regression analysis was conducted. PD patients and healthy controls differed significantly in the EC component Preparedness as well as in the neuropsychological test battery scores. PD patients showed lower scores in cognitive tests and a lower score in Preparedness compared to healthy adults. The output of the regression analysis showed that the extent to which the neuropsychological tests relate to the ECI components is low.